2013
DOI: 10.1007/s11999-013-3170-9
|View full text |Cite
|
Sign up to set email alerts
|

Image Guided Core Needle Biopsy of Musculoskeletal Lesions: Are Nondiagnostic Results Clinically Useful?

Abstract: Nondiagnostic core needle biopsy results in musculoskeletal lesions are not entirely useless. At times, they can be supportive of benign processes and can help avert unnecessary surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 11 publications
4
38
0
Order By: Relevance
“…These results were useful in clinical practice in around 60% of the cases, and should not be considered flaws [60]. In a study it was showed that they were helpful mostly in asymptomatic versus symptomatic lesions (84% vs 55%), non-aggressive versus aggressive (72% vs 45%) and in case evaluated pre-biopsy as "likely to be benign" versus "suspicious for malignancy" (74% vs 40%) [60].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These results were useful in clinical practice in around 60% of the cases, and should not be considered flaws [60]. In a study it was showed that they were helpful mostly in asymptomatic versus symptomatic lesions (84% vs 55%), non-aggressive versus aggressive (72% vs 45%) and in case evaluated pre-biopsy as "likely to be benign" versus "suspicious for malignancy" (74% vs 40%) [60].…”
Section: Discussionmentioning
confidence: 98%
“…US was mostly used for the first two types of BL (lytic) [42] when biopsy was performed with cutting or fine needles. Sclerotic lesions were associated with the lowest diagnostic yield indifferent of the guiding method (US or CT), and were biopsied with trephine needles -Jamshidi [48], Ostycut [35,42], Bonopty [60] -allowing drilling in the bone cortex, followed by cutting biopsy or aspiration with coaxial technique. For the last type of BL (without alteration of the bone cortex) biopsy was performed also with the trephine needles usually under radiological guidance, but also with US guidance in some studies [42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations